DETERMINANTS OF SHARIA FINANCE INCLUSION IN THE STUDENT ENVIRONMENT - Pinilih, Muliasari; Shaferi, Intan; Purwadi, Purwadi; Sejati, Maulita Nur; Sain, Juwita Anggraini (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2024)
This study aimed to analyze the influence of financial literacy, technology, and self-efficacy on Islamic financial inclusion. The investigation further examined the differences in Islamic inclusion levels across different student groups. In order to achieve the stated objective, data was collected through the administration of a questionnaire to 174 students, after which an analysis was carried out using the t-test, F-test, and independent test differential approaches. The obtained results showed that financial literacy had a partial influence, while financial technology had no effect on Sharia financial inclusion. Accordingly, financial self-efficacy was observed to influence Islamic financial inclusion only in the business and management student group and not in the non-business and management group. It is also important to state that the analysis results did not show any difference in Islamic financial inclusion and financial literacy, but a difference was found between financial technology and financial self-efficacy of the two groups.